1995
DOI: 10.1042/bj3090781
|View full text |Cite
|
Sign up to set email alerts
|

Spermine induces haemoglobin synthesis in murine erythroleukaemia cells

Abstract: The naturally occurring polyamine spermine induces haemoglobin synthesis in murine erythroleukaemia (MEL) cells. Haemoglobin production was accompanied by accumulation of cytoplasmic beta-globin mRNA and growth inhibition, but not by cell-cycle block or changes in cell volume. Hexamethylene-bisacetamide (HMBA), a well known differentiating agent, also induces haemoglobin production, but causes a G1 block and decreases cell volume. These findings indicate that HMBA and spermine affect MEL cells differently, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…31,32 On the other hand, polyamines, which are produced from L-ornithine through L-arginine, induce hemoglobin synthesis in murine erythroleukemia cells. 33 In contrast, there is a report that amino acid starvation induces differentiation through an amino acid response element like C/EBP homologous protein, 34 but this seems to be a different phenomenon not involving a transporter.…”
Section: Discussionmentioning
confidence: 96%
“…31,32 On the other hand, polyamines, which are produced from L-ornithine through L-arginine, induce hemoglobin synthesis in murine erythroleukemia cells. 33 In contrast, there is a report that amino acid starvation induces differentiation through an amino acid response element like C/EBP homologous protein, 34 but this seems to be a different phenomenon not involving a transporter.…”
Section: Discussionmentioning
confidence: 96%
“…Among polyamines, spermine was reported to induce hemoglobin synthesis in murine erythroleukemic cell line MEL cells. 18) Since K562 cells were differentiated by butyrate, in the present study the effect of polyamines on the butyrate-dependent differentiation of K562 cells was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it was shown that polyamine itself could not induce the growth or differentiation of K562 cells to erythrocytes and the differentiation mechanism of human leukemia K562 cells was apparently different from that observed in mouse erythroleukemic MEL cells. 18) Next, we investigated the effect of polyamines in the presence of sodium butyrate, whether polyamines could complement the role of L-arginine. However, polyamines did not induce any differentiation or proliferation of K562 cells in the absence of L-arginine and rather reduced the cell growth depending on the examined concentration (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamines are biological polycations that play a major role in cell growth and differentiation [1,2]. In murine erythroleukaemia (MEL) cells, spermine and synthetic polyamine analogues induce haemoglobin synthesis [3,4]. In a previous study, we related the ability of polyamine analogues to induce haemoglobin synthesis in this cell line to the number of cationic charges they possess [4].…”
Section: Introductionmentioning
confidence: 99%